Psychological responses to the new terrorism : a NATO-Russia dialogue - Wessely, Simon; Krasnov, Valeriĭ (NATO security through science series. Human and societal dynamics ;, 2005)
Terrorism is to create a state of terror and fear. This book is concerned with the consequences of acts of terror, and their impact on populations. It describes what citizens, professionals and governments can do to mitigate the consequences. It focuses more on culture and place specific reactions than the timeless or universal trauma reactions.